2015
DOI: 10.1097/mbc.0000000000000331
|View full text |Cite
|
Sign up to set email alerts
|

Acute myocardial infarction as a finding of acute promyelocytic leukemia–related coagulation disorder

Abstract: Acute promyelocytic leukemia (APL) has one of the most favorable prognoses among other leukemia subtypes. However, the major cause of mortality in APL is disseminated intravascular coagulation at the presentation. We present a case of acute myocardial infarction (MI) at the time of APL diagnosis before treatment. The patient suffered from chest pain, sweating and giddiness. He was hypoxic, hypotensive and bradycardic. ECG showed inferior MI. Unfractioned heparin infusion (850 U/h) was started and 5 min after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“… 3 , 11 Um relato de caso afirmou que IAMSST inferior se desenvolveu em um paciente LPA com CID, e a síndrome coronariana aguda regrediu dramaticamente em um curto período de tempo com infusão de heparina. 12 Os autores consideraram que a etiologia da síndrome coronariana aguda do paciente foi devida à CID e não à ruptura da placa aterosclerótica. 12 Casos de IAM não trombótico secundário a hiperleucocitose e leucostase e IAM trombótico secundário a CID têm sido relatados na literatura.…”
Section: Discussionunclassified
See 3 more Smart Citations
“… 3 , 11 Um relato de caso afirmou que IAMSST inferior se desenvolveu em um paciente LPA com CID, e a síndrome coronariana aguda regrediu dramaticamente em um curto período de tempo com infusão de heparina. 12 Os autores consideraram que a etiologia da síndrome coronariana aguda do paciente foi devida à CID e não à ruptura da placa aterosclerótica. 12 Casos de IAM não trombótico secundário a hiperleucocitose e leucostase e IAM trombótico secundário a CID têm sido relatados na literatura.…”
Section: Discussionunclassified
“… 12 Os autores consideraram que a etiologia da síndrome coronariana aguda do paciente foi devida à CID e não à ruptura da placa aterosclerótica. 12 Casos de IAM não trombótico secundário a hiperleucocitose e leucostase e IAM trombótico secundário a CID têm sido relatados na literatura. 13 , 14 Curiosamente, neste caso que apresentamos, não houve hiperleucocitose, leucostase ou CID.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…It was found that patients with acute promyelocytic leukemia have been reported in many literatures. [11,12] On the one hand, APL is the underlying cause of CHD, and APL-associated thrombosis events are associated with leukemia and the interaction between malignant promyelocytes and host cells. [13] On the other hand, APL patients with bleeding are well known, high incidence of early hemorrhagic deaths remains the greatest contributor to chemotherapy failure.…”
Section: Discussionmentioning
confidence: 99%